Eczema and Food Allergies in Children: A Systematic Review of Developmental Outcomes - Aprilea, Noor Adha; Sofia, Norlaila; Rusmilawaty, Rusmilawaty; Dewi, Vonny Khresna; Salaya, Lulu (Interest : Jurnal Ilmu Kesehatan, 2026)
Background: Pediatric eczema (atopic dermatitis; AD) and food allergies (FA) are rising globally and share immune pathways that extend harm beyond the skin to growth, cognition, and social development—yet no synthesis has examined all three developmental domains exclusively using primary empirical evidence. This systematic review aimed to determine whether children with AD and/or FA exhibit: (1) impaired physical growth; (2) adverse cognitive and neurodevelopmental outcomes; and (3) elevated rates of behavioral and social difficulties compared to unaffected peers. Methods: A systematic search of MEDLINE, Embase, Scopus, Web of Science, and grey literature repositories identified 210 records after deduplication. Following title/abstract screening and full-text review of 98 articles, 35 primary empirical studies—spanning diverse designs—met inclusion criteria. Systematic and narrative reviews were excluded. Results: Twenty-two of 35 studies reported impaired physical growth, including lower height, weight, BMI, and head circumference z-scores, with 18 reaching statistical significance. Deficits were most pronounced in children with severe or persistent disease and multiple allergen restrictions. Cognitive and neurodevelopmental impacts were identified in 13 studies, with effects varying by developmental domain and disease severity. Behavioral and social difficulties appeared in 10 studies, predominantly linked to severe disease and sleep disruption. Conclusion: Eczema and food allergies impair child development through interconnected immune, nutritional, and psychosocial pathways. Multidisciplinary care and early intervention are essential; clinicians should routinely refer affected children to pediatric dietitians. Future research should prioritize large longitudinal studies incorporating standardized neurodevelopmental assessments and biomarkers.